2021
DOI: 10.1172/jci.insight.148643
|View full text |Cite
|
Sign up to set email alerts
|

T cell–derived tumor necrosis factor induces cytotoxicity by activating RIPK1-dependent target cell death

Abstract: TNF ligation of TNF receptor 1 (TNFR1) promotes either inflammation and cell survival by (a) inhibiting RIPK1’s death-signaling function and activating NF- κ B or (b) causing RIPK1 to associate with the death-inducing signaling complex to initiate apoptosis or necroptosis. The cellular source of TNF that results in RIPK1-dependent cell death remains unclear. To address this, we employed in vitro systems and murine models of T cell–dependent transplant or tumor rejection in which target c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 90 publications
(149 reference statements)
1
6
0
Order By: Relevance
“…45 The fact that BK infections occurred in the absence of transplant-associated IS and in native kidneys in this inflammatory bowel disease cohort treated with anti-TNF supports the conclusion that TNF participates in preventing BK virus infection/reactivation. TNF's established proinflammatory effects, its ability to activate 46 NK cells that have a known protective function against BK infection, 47,48 and reports that TNF contributes to T cell 18 and natural killer cell cytotoxic killing 49 of infected target cells suggest mechanistic links to account for our observations. Further supporting a mechanistic connection between TNF preventing BK infection, in vitro analyses of BK infection of proximal tubular cells and molecular analyses of BK infected kidneys show active BK virus infection is associated with lower TNF expression.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…45 The fact that BK infections occurred in the absence of transplant-associated IS and in native kidneys in this inflammatory bowel disease cohort treated with anti-TNF supports the conclusion that TNF participates in preventing BK virus infection/reactivation. TNF's established proinflammatory effects, its ability to activate 46 NK cells that have a known protective function against BK infection, 47,48 and reports that TNF contributes to T cell 18 and natural killer cell cytotoxic killing 49 of infected target cells suggest mechanistic links to account for our observations. Further supporting a mechanistic connection between TNF preventing BK infection, in vitro analyses of BK infection of proximal tubular cells and molecular analyses of BK infected kidneys show active BK virus infection is associated with lower TNF expression.…”
Section: Discussionmentioning
confidence: 56%
“…Among the mediators implicated in the pathogenesis of DGF is TNF, a pleiotropic cytokine produced by multiple cell types, including monocytes, macrophages, 17 T cells, 18 and endothelial cells. 19 TNF was originally identified by its ability to induce necrosis of implanted tumors in vivo (hence its name), 20 but subsequent studies linking TNF's proinflammatory function to multiple inflammatory diseases has resulted in the development of effective TNF-neutralization therapies currently in use for rheumatoid arthritis 21,22 and inflammatory bowel disease.…”
mentioning
confidence: 99%
“…Our study also found a meaningful correlation between NecroticScore and immune checkpoint expression. CHUN, N et al ( Chun et al, 2021 ) found activation of the necroptosis-related molecules synergizes with anti-PD1 administration to destroy checkpoint blockade-resistant murine melanoma in murine melanoma. A clinical trial ( Topalian et al, 2012 ) proved to be more effective in the treatment of anti-PD1 antibodies, which were strongly associated with higher expression of PD-L1 and PD-1 checkpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Necroptosis is initiated by the binding of specific ligands to their respective receptors, such as TNF receptors, TLR receptors, and others [ 26 ]. This binding results in the recruitment of several adaptor proteins, forming complex I.…”
Section: Non-apoptotic Mechanisms In Melanomamentioning
confidence: 99%
“…In addition, necroptosis also increases the infiltration of T cells, including CD 4+ and CD 8+ T cells, into the tumor microenvironment [ 84 ]. Conversely, TNF released by T cells can activate RIPK1-dependent necroptosis in tumor cells [ 26 ]. Notably, CAFs can also respond to necroptosis.…”
Section: Interactions In the Tumor Microenvironment (Tme)mentioning
confidence: 99%